Inflammatory basis for dry eye disease flares. (December 2020) - Perez, Victor L.; Stern, Michael E.; Pflugfelder, Stephen C.
Abstract: Most patients with chronic dry eye disease (DED) have episodic flares, which can be triggered by a variety of activities and environmental stresses. These flares are typically associated with rapid exacerbation of discomfort symptoms, followed by prolonged elevation of inflammation. In an acute flare, ocular surface inflammation begins with a nonspecific innate immune response, in some cases followed by a slower but more specific adaptive immune response. At the ocular surface, epithelial cells are central to the innate immune response, and we discuss their role in DED flares alongside the other core components. Epithelial cells and other cells of the innate response (neutrophils, monocytes, macrophages and dendritic cells) trigger flares in response to increased osmolarity, detected via pattern receptors on their cell surface. Ultimately, downstream signaling pathways activate innate and adaptive immune responses, with consequent inflammation and symptoms. In chronic DED, pathogenic T cells have infiltrated the ocular surface tissues. The established adaptive immune response is likely to lead to flare-ups at lower thresholds of stress, with inflammation maintained over a longer period. Increased understanding of the inflammatory cascades activated during a flare may guide management and improve outcomes. Highlights: Episodic inflammatory flares occur in most patients with chronic dry eye disease. Flares typically show rapid onset followed by prolonged exacerbation of symptoms. Flares result from complex inflammatory cascades. Increased understanding of flares may guide management and improve outcomes.